The Interventional Effect of Quiet Time Protocol on the Sleep Status of Premature Neonates Admitted to the NICU - Kimiya Sabagh; Fereshteh Ghaljaei (Mashhad University of Medical Sciences, 2024)
Background: Most infants born prematurely are admitted to the NICU for their survival, an environment that is rich in stressors that has non positive effect on the sleep and wakefulness condition. The goal of this study was evaluating the effect of the QTP intervention on the sleep status of premature neonates admitted to the NICU. Methods: This study was semi-experimental and 62 premature babies hospitalized in NICU, who were selected by available sampling method. The tools used included demographic information questionnaire and Als sleep and wakefulness tool. Infants in two groups were evaluated in 3 stages. before, during and after the intervention in the evening shift from 15:00 to 17:00 for 60 minutes. The data was analyzed using SPSS software (version 22). A  p value of less than 0.05 was considered statistically significant. The validity of the mentioned tool was investigated according to the content method according to the study of Rajaei in 2013 under the title of investigating the sleep-wakefulness of premature infants and its relationship with demographic characteristics, and the reliability of the tool was also investigated according to the same study. Results: The chi-square test showed that the variable frequency of deep sleep (type A) before (P=1)and after (P=0.05) the intervention in the two groups did not have a statistically significant difference and just during the intervention has a statistically significant difference (P<0.001). Comparison of the distribution of the frequency of deep sleep (type B) before, during and after the intervention in 2 groups shows that before the intervention, deep sleep (type B)  was not observed in the two groups. However, in the intervention group, 58.1% had deep sleep during the intervention and 6.5% after the intervention. The control group did not have deep sleep (type B) in these three time periods. Conclusion: Considering the effectiveness of QTP in reducing environmental stimuli and improving sleep status, implementation of these items is recommended as a standard care to reduce stress, improve growth and development of preterm infants in the nicu.